2010
DOI: 10.1007/s00296-010-1434-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of tumor necrosis factor-α promoter region for susceptibility to HLA-B27-positive ankylosing spondylitis in Korean population

Abstract: This study designed to assess the relationship between tumor necrosis factor (TNF)-α promoter polymorphisms and disease susceptibility to human leukocyte antigen (HLA)-B27-positive ankylosing spondylitis (AS). One hundred and nineteen HLA-B27(+) AS patients, 95 HLA-B27(+) healthy controls, and 135 random healthy controls were enrolled in this study. Six single nucleotide polymorphisms (SNPs) of the TNF-α promoter at positions -1031T/C, -863C/A, -857C/T, -646G/A, -308G/A, and -238G/A were analyzed. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…Of the 253 publications retrieved initially, 10 studies, which involved 987 ankylosing spondylitis patients and 1041 controls (Cai et al 2009; Chatzikyriakidou et al 2009; Chen et al 2004; Chung et al 2011; Ji et al 2013; Li et al 2007; Lin 2007a, b; Mei et al 2009; Tong et al 2012; Yang et al 2007), were ultimately identified. Figure 1 shows the flowchart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 253 publications retrieved initially, 10 studies, which involved 987 ankylosing spondylitis patients and 1041 controls (Cai et al 2009; Chatzikyriakidou et al 2009; Chen et al 2004; Chung et al 2011; Ji et al 2013; Li et al 2007; Lin 2007a, b; Mei et al 2009; Tong et al 2012; Yang et al 2007), were ultimately identified. Figure 1 shows the flowchart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…In the present meta-analysis, we included 10 studies (Cai et al 2009; Chatzikyriakidou et al 2009; Chen et al 2004; Chung et al 2011; Ji et al 2013; Li et al 2007; Lin 2007a, b; Mei et al 2009; Tong et al 2012; Yang et al 2007) that addressed the association between TNF-α −857 C/T polymorphism and risk of developing ankylosing spondylitis. The results of this meta-analysis indicated that T allele carriers presented a 1.76-fold higher risk of developing ankylosing spondylitis than C allele carriers, CT genotype carriers presented a 2.30-fold higher risk than CC genotype and TT + CT genotype carriers presented a 2.26-fold higher risk than CC genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relation between TNF-α SNPs and AS have shown controversial results. For example, TNF-α polymorphisms had no independent effect on AS susceptibility (Chung et al 2011; Li et al 2010) but their modulating effect on TNF-α expression were well relevant to the phenotypic diversity in AS (Lee and Song 2009; Poddubnyy et al 2011). In contrast, Vargas-Alarcón et al (2006) and Shiau et al (2007) showed an association of −308G/A polymorphism with susceptibility to AS.…”
Section: Association Between Tnf-α Genetic Polymorphisms and Autoimmumentioning
confidence: 99%
“…In contrast, Vargas-Alarcón et al (2006) and Shiau et al (2007) showed an association of −308G/A polymorphism with susceptibility to AS. Moreover, the A allele was thought to have a protective role against AS (Chung et al 2011; Nossent et al 2014), and was associated with a lower risk of developing AS, and with the age at disease onset, disease severity and response to anti-TNF treatment (Manolova et al 2014). …”
Section: Association Between Tnf-α Genetic Polymorphisms and Autoimmumentioning
confidence: 99%
“…TNFRII is specifically involved in the stimulation of T and B lymphocytes (Vandenabeele et al, 1995), and the exon 6 variation located at nt587 is a T to G SNP that results in the substitution of methionine by arginine at codon 196. Polymorphisms of the TNF-α gene have been intensively studied (Li et al, 2010;Chung et al, 2011), among which, the TNFRII nt587 polymorphism has been frequently reported in chronic autoimmune disease such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and alcoholic liver disease. Komata et al (1999) demonstrated an association between SLE and the G allele of TNFRII nt587 in a Japanese population.…”
Section: Tnfrαnt587mentioning
confidence: 99%